Recent fabrications and applications of cardiac patch in myocardial infarction treatment. Issue 2 (16th September 2021) - Li, Mei; Wu, Hao; Yuan, Yuehui; Hu, Benhui; Gu, Ning
Abstract: Myocardial infarction caused by coronary artery obstruction results in the loss of heart muscle, which is subsequently replaced by scar tissue with limited therapeutic options. Cardiac patch based therapy has emerged as a promising strategy for the treatment of severe myocardial infarction. They are designed to be attached to the surface of the heart, that is, they are meant to "patch" the injured heart, thus restoring the damaged or failing myocardium locally through mechanical and regeneration support. The engineered three‐dimension cardiac patch is composed of biomaterial scaffolds with/without cells or inducible factors, which is typically manufactured by decellularize extracellular matrix, electrospinning, three‐dimension printing, hydrogels, or by stacking cell sheets. In this review, we outline the latest advances of the construction methods and beneficial effects of cardiac patches used in animal and clinical treatment of cardiovascular diseases, especially in myocardial infarction. We discuss the cell souring of cell‐based patches, the types of biomolecules for cell‐free patches, and their engineering methods. In addition, the method of implanting the cardiac patch to the injured heart is also described. Finally, we briefly outlook the future challenges and probable solutions in this area. Abstract : The cardiac patch exhibits priority in treating myocardial infarction with the ability to afford mechanical support and stimulate remolding pathways, realized by the scaffold properties and the transported stem cells or biological components. The fabrication methods, delivery approaches, and therapeutic cells/factors of cardiac patches and their beneficial effects in treating myocardial ischemia are outlined in this review.